Research - Based Technology Education – the EDURES Partnership Experience - Roman Wdowik; Marek Magdziak; Andrzej Dzierwa; Barbara Ciecińska; Przemysław Podulka; Jolanta Litwin; Artur Bełzo; Artur Borowiec; Piotr Nazarko; Agnieszka Wiater; Angelos Markopoulos; Faramarz Hojati; et al. (Technologia i Automatyzacja Montażu)
Thepaper presents the state regarding practices in teaching at partner universities of the EDURES project and current approaches supporting research-based education. It also presents the needs of various groups of stakeholders formulated on the basis of survey results. Moreover, the paper proposes tools and strategies which are useful if research results are implemented in teaching programmes at technical universities (research-based lectures, e-learning, web portal methodologies, wizards, etc). It is finally stated that research-results implementation into teaching processes is possible by the use of various tools and approaches proposed by the EDURES partnership and has thepotential to be appreciated by students, academics and external stakeholders.